Peran AALCO dalam Pemulihan Aset Kejahatan Transnasional: Perspektif Hukum tentang Kerjasama Asia-Afrika - Siswanto, Carissa Amanda; Kartiko, Nafis Dwi (Jurnal Penelitian Hukum De Jure, 2025)
The Asia-African Legal Consultative Organization (AALCO), as an intergovernmental organization in Asia and Africa, possesses significant potential to facilitate cooperation among member states in combating transnational crimes and recovering assets. The objective of this study is to explore and analyze the role of the Asia-African Legal Consultative Organization (AALCO) in the international legal framework governing asset recovery of assets arising from criminal activities. The research method used is normative-dogmatic juridical with statutory, conceptual, and comparative approaches. This research uses primary legal sources, such as laws and international treaties, as well as secondary legal sources, such as journals, articles, books, and comments on judges' decisions. The findings of this study indicate that AALCO has an important role in facilitating cooperation among its member states for the recovery of assets derived from criminal activities. AALCO has developed mechanisms such as conventions and guidelines to guide member states in asset recovery. However, this research also found limitations, such as the lack of harmonization of laws among the member states and limited institutional capacity in some states. In addition, there are still challenges in cross-jurisdictional coordination and a lack of public awareness on the importance of asset recovery. In light of these findings, this research recommends AALCO to strengthen a uniform legal framework and improve training and capacity building for law enforcement. In addition, AALCO also needs to strengthen information networks among member states and build partnerships with international organizations. By implementing these recommendations, AALCO can be more effective in supporting efforts to recover assets derived from criminal conducts in the Asia and Africa region.